Nutrition assessment in surgical patients: The strategic way to improve outcomes - Kaweesak Chittawatanarat (Indonesian Nutrition Association, 2026)
Malnutrition remains a significant but often under-recognized challenge in the management of surgical patients worldwide. It is estimated that a substantial proportion of patients undergoing major surgery, particularly those with gastrointestinal or oncologic diseases, suffer from some degree of malnutrition1,2. The physiological stress induced by surgery, characterized by a hypermetabolic state and systemic inflammatory response, exacerbates existing nutritional deficits3. This synergistic effect leads to impaired immune function, delayed wound healing, increased muscle wasting, and a higher predisposition to postoperative complications such as sepsis and anastomotic leakage1,4. Consequently, malnutrition is directly linked to prolonged hospital stays, increased healthcare costs, and higher mortality rates [2, 5]. Therefore, early and systematic nutrition assessment is no longer optional but a fundamental pillar of perioperative care4.